PHOTOMETRY IN UBVRIJHKL OF THE EARLY MAIN SEQUENCE IN THE PLEIADES DOWN TO GOV - IRIARTE ERRO, B (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1971)
Photoelectric photometry in UBVRIJHKL of thirthy-nine members of the Pleiades cluster was obtained in an attempt to determine the dependence of interstellar extinction on wavelength throughout the cluster. In the process of the investigation infrared exce
BOL OBS TONAN TACUB
Keywords: PHOTOMETRY, UBVRIJHKL, EARLY MAIN, SEQUENCE, PLEIADES DOWN; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOMETRIA